Recessions, income inequality and the role of the tax and benefit system - Jonathan Cribb; Andrew Hood; Robert Joyce (Institute for Fiscal Studies (IFS), 2017)
It is now around a decade since the financial crisis that triggered the Great Recession of 2008-09. In many respects, the impacts of this recession on the living standards of UK households have been unusually severe. Median household income is now around 15% below its long-run trend, having grown by only around 5% over the past decade. However, one dimension in which the Great Recession has not had a deleterious impact is income inequality. In this report, we seek to understand why past recessions have had such different effects on income inequality. We also examine the potential impact of the next labour market downturn on the distribution of household incomes.
Keywords: 330